Insolvency and Legal Gaps in Unlegalized Murabahah Contracts - Mahardika, Kamila Dwi; Hutomo, Putra; Anwar, Khoirul (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2025)
This study aims to examine and analyze the legal consequences of murabahah agreements made underhand without legalization or waarmerking when the debtor fails to pay and to examine and analyze the legal certainty of murabahah agreements made underhand without legalization or waarmerking between the debtor and creditor. Murabahah agreements are often made underhand without legalization or waarmerking by a Notary to reduce contract costs and can be detrimental to creditors if the debtor defaults so that they must meet the terms of the agreement and sharia principles to obtain legal force in Court. The method used in the study is normative legal research. The research approaches used are the Legislation Approach, Case Approach, Analytical Approach, Conceptual Approach and the technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The technique of analyzing legal materials is carried out with systematic interpretation, analogy construction and legal construction methods. From the research results, it was found that the murabahah agreement made underhand without legalization or waarmerking by a Notary has legal consequences in the form of binding the parties which gives rise to rights and obligations for the parties. The murabahah agreement made underhand without legalization or waarmerking by a Notary has legal certainty if it meets the terms of the agreement and meets the principles of sharia but does not have perfect legal proof. The murabahah agreement should be made with an authentic deed to obtain legal certainty and legal consequences in the form of perfect legal proof if in the future the debtor commits a default in the form of failure to pay.